A helical naphthopyran dopant for photoresponsive cholesteric liquid crystals. Issue 1 (5th December 2016) - Kim, Yuna; Frigoli, Michel; Vanthuyne, Nicolas; Tamaoki, Nobuyuki
Abstract : Photoisomerization of helical naphthopyran in cholesteric liquid crystals exhibited huge helical twisting power switching of over 90% resulting in significantly efficient rotational motion of micro-sized objects. Abstract : The first photoresponsive cholesteric liquid crystal comprising a photoisomerizable helical naphthopyran derivative dopant and a nematic liquid crystal is reported. An unprecedented helical twisting power switching ratio of over 90% allowed us to demonstrate multi-cycle rotational motion of micro-objects by UV light irradiation.